Imigração, Desenvolvimento e Competitividade em Portugal - Maria Conceição Ramos (2007)
The study of migrations and its relation to the development of countries has become more important with globalization. The main inter-relations observed occur around a few major themes: a better use of migrant human resources to promote economic development; migrants financial transfers; return migrations. Portugal, being simultaneously a receptor and producer of international migrations, presents nowadays a specific situation in the European Union and in the growing globalization context of economies and employment. What role may migrants play in the adjustment of work markets? What effects does it cause in Portuguese economy and enterprise competitiveness? What is the dynamics of migrant entrepreneurialship in Portugal?